Health Education, Screening and Diabetic Foot Excercise in Cimanggu District, Bogor - Henri Setiawan; Suhanda Suhanda; Elis Roslianti; Andan Firmansyah; Ade Fitriani; Dadi Hamdani; Andika Abdul Malik; Irma P. Arisanty; Navis Aulia Rahman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The emergence of the COVID-19 disease outbreak and the government's PPKM regulations have forced people to work remotely from their homes, making them less physically active and exercising so that they can be at risk of triggering the emergence of various diseases in the future, one of which is diabetes mellitus. So STIKes Muhammaduyah ciamis Working in collaboration with Moist Care Clinic Bogor feels It is crucial and required to provide education about the risk of diabetes, screening for diabetic feet as early detection and diabetic foot exercise as a good physical activity for the feet to prevent diabetic sores. This community service project's goal is to provide health counseling, foot screening, and foot exercises for diabetes mellitus in the Cimanggu District Community, Bogor. This community service is intended for the Cimanggu District Community in Bogor. The activities are carried out within a period of 1 month starting from January 6 to February 4, 2022, Preparation, execution, and evaluation are the stages of an activity. Preparation includes a field survey and activity permit. Doctors from the Moist Care Clinic practiced foot screening as part of the implementation. Health Counseling by Lecturers from STIKes Muhammadiyah Ciamis and Diabetic Foot Exercises by DIII Nursing Study Program Students from STIKes Muhammadiyah Ciamis. Each stage of an activity is evaluated by compiling and drawing conclusions from the data collected, with the Moist Care Clinic following up on these findings in the future. The results of the activity are the implementation of diabetes foot screening, diabetes health counseling, and diabetes foot exercises. Implementing activities are lecturers, nurses, and students and assisted by the Cimanggu sub-district community.